2004
DOI: 10.1590/s0066-782x2004001400002
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco e morbimortalidade associados à fibrilação atrial no pós-operatório de cirurgia cardíaca

Abstract: ObjectiveTo determine the incidence of atrial fibrillation in the postoperative period of cardiac surgery, its impact on morbidity, mortality, and hospital stay, and ConclusionThe incidence of atrial fibrillation in the postoperative period of cardiac surgery was high and caused a significant increase in morbidity, mortality, and the length of hospital stay. Among the independent risk factors, excessive fluid balance is significant. The use of beta-blockers was identified as a protective factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…Given the data found of higher morbidity associated with PAF, it is understandable to expect an increase in the duration of stay in days, as observed in our study (19.11 ± 15.87 vs. 12.58 ± 12; p = 0.01). Data from a Brazilian group showed similar results of a more extended hospital stay in days (16.9 ± 12.3 vs. 9.2 ± 4, p <0.001) 31 .…”
Section: Discussionmentioning
confidence: 52%
“…Given the data found of higher morbidity associated with PAF, it is understandable to expect an increase in the duration of stay in days, as observed in our study (19.11 ± 15.87 vs. 12.58 ± 12; p = 0.01). Data from a Brazilian group showed similar results of a more extended hospital stay in days (16.9 ± 12.3 vs. 9.2 ± 4, p <0.001) 31 .…”
Section: Discussionmentioning
confidence: 52%
“…With respect to prevention of thromboembolic phenomena, POAF is associated with a higher risk of stroke, ranging from 1.9% to 18.2%, that emphasizes the use of therapeutic anticoagulation [21,34,35] . Our group found a stroke incidence of 11.1% in patients who developed POAF vs. 1.9% of incidence in patients who maintained sinus rhythm [36] . Patients with left ventricular dysfunction, previous history of thromboembolism, and systemic arterial hypertension are at greater risk for thromboembolic complications.…”
Section: Anticoagulation Strategies For the Management Poafmentioning
confidence: 49%
“…Silva et al [22] found total positive fluid balance in the first 24 hours after surgery as a risk factor for AF. This study demonstrated that there is a 1% risk of developing AF for each 1 ml above the average of total fluid balance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the effectiveness in the implementation of pharmacological measures to prevent AF after cardiac surgery [22,30,31]. It is believed that a risk score for the incidence of AF may guide the conduct of clinical and surgical approaches, indicating the best candidate to receive these measures.…”
Section: Discussionmentioning
confidence: 99%